Dynamics of Temperature Changes in Thermophille Phase of Composting Process in The Aspect of Sanitary Condition of Obtained Material (Agricultural Engineering, 2017)
A condition of obtaining compost with proper sanitary parameters is achieving the organic recycling process temperature which exceeds 7°C. The objective of the paper was to determine the temperature course in the compost tank for organic recycling of dead poultry in relation to the applied structure forming material. Wheat, oat, barley, rapeseed and corn straw were used as a structure-forming material. A measuring system was equipped with a probe with a temperature sensor with precision of ±0.15°C, transducer and data recorder. Results were prepared with the use of the analysis of variance at the level of significance of α=0.05. Statistically significant differences of the temperature value in the thermophille phase of the composting process between combinations of the experiment were indicated. In all investigated combinations of the experiment, achievement (or exceeding) the temperature value of 70°C of the compost mass was reported.